Feasibility of combination of Gun-Chil-Jung and cytokine-induced killer cells-based immunotherapy for terminal hepatocellular carcinoma patient: a case report - Park, Chan-Ran; Bae, Hye-Ri; Lee, Ga-Young; Son, Chang-Gue; Cho, Jung-Hyo; Cho, Chong-Kwan; Lee, Nam-Hun (Frontiers in Pharmacology, 2023)
Introduction: Terminal-stage hepatocellular carcinoma (HCC) is inoperable and currently has no form of adjuvant therapy. This study examined the anticancer herbal extract Gun-Chil-Jung (GCJ) combined with cytokine-induced killer (CIK)-cell-based immunotherapy as a palliative therapy for terminal HCC. We report the case of an HCC patient with extended overall survival and improved symptoms and tumor marker levels following combination therapy with GCJ and CIK cell-based immunotherapy.Baseline Characteristics: From March to July 2020, a 57-year-old man who had been diagnosed with HCC underwent combination treatment with GCJ and CIK cell-based immunotherapy. By August 2021, he was prescribed GCJ. After treatment, the patient's condition was evaluated with respect to overall survival, tumor markers, symptoms, abdominal computed tomography findings, chest x-ray results, and Eastern Cooperative Oncology Group (ECOG) grade.The patient's overall survival, tumor marker levels, ECOG grade, and symptoms, including ascites, lower limb edema, jaundice, pleural effusion, and fatigue, were largely alleviated.We expect that this combination therapy may be an option for palliative therapy of terminal HCC.